Can blood pressure be measured without undressing patients ? - Pierre-Yves Durand; Typhaine Le Hegarat; Thibault Gutter (RDPLF, 2021)
The guidelines recommend that the technique of measuring arterial blood pressure requires positioning the cuff on a bare arm, without rolled-up sleeve. These recommendations are sometimes difficult to apply in routine practice, as in dialysis centers where the measurement is repeated in fragile patients. In this study, we assess the validity of the blood pressure measurement with a cuff positioned on a bare arm, compared to a cuff positioned on several layers of clothing. A total of 1,224 blood pressure measurements were taken in 51 dialysis patients over a period of one month, 6 measurements per week, i.e. 24 measurements per patient. The patients wore their ordinary clothes suitable for a winter season. Thus, 612 measurements were taken with a cuff on a bare arm, and 612 measurements with a cuff on clothing. The mean systolic pressures were 121.9 and 123.5 mmHg, respectively when the cuff was placed on clothing and bare skin. The mean diastolic pressure was 60.1 and 60.5 mmHg, respectively. The observed difference does not reach the level of statistical significance with respectively p = 0.168 and p = 0.135. The same is true for mean arterial pressure, with 80.6 and 81.5 mmHg respectively (p = 0.142). The difference observed does not justify the undressing of patients for whom this procedure is difficult, uncomfortable or painful.